Labor of Minors in Industrial of Ukrainian Lands (19th – Early 20th Century) - Shandra , Iryna; Birova, Olha (Studia Historiae Oeconomicae, 2023)
At the present stage, the phrase “labor of minors” sounds alarming and is a sign of the low economic and cultural development of society. For the period of industrialization of the 19th – early 20th century this phenomenon was by no means a rarity, but rather one of the components of economic modernization. The Ukrainian lands were no exception in this regard, child and adolescent labor was used in coal, metallurgical, chemical and other industries. This study is based on workers’ memories of their teenage years, memories of mining engineers, factory inspectors, public figures, as well as, albeit very scattered, statistics on the employment of minors in industry in the second half of the 19th – early 20th century. The most significant and, in this regard, reflected in the memoirs of participants in the production process, were such aspects of the work of minors as working conditions, wages, “professions” of minors, their employment statistics, the evolution of labor legislation and numerous violations of approved norms. The complex conclusion is that it took a long mutual development of public opinion, legislation and family foundations to eradicate the work of minors in industry.